Filsafat Ilmu sebagai Landasan Holistis Pengembangan Ilmu Psikologi - Juneman Juneman; Yosef Dedy Pradipto (Bina Nusantara University, 2013)
Psychology has long been accepted by many scholars as a science. Nevertheless, intensive readings on philosophy of science and psychology in Indonesia are rarely found. Meanwhile, there are not many professional psychologists nor psychology scientists deliver a course on Philosophy of Science in the faculties and study programs of psychology. The common argument proposed is that both psychologists and lecturers on psychology are not well qualified nor confident enough to teach the Philosophy of Science subject, as if the subject